Harmful algal bloom-related 311 calls, Cape Coral, Florida 2018-2019 - Christopher K. Uejio; Elaina Gonsoroski; Samendra P. Sherchan; Leslie Beitsch; E. W. Harville; C. Blackmore; K. Pan; Maureen Y. Lichtveld (IWA Publishing, 2022)
Harmful algal blooms (HABs) can adversely impact water quality and threaten human and animal health. People working or living along waterways with prolonged HAB contamination may face elevated toxin exposures and breathing complications. Monitoring HABs and potential adverse human health effects is notoriously difficult due to routes and levels of exposure that vary widely across time and space. This study examines the utility of 311 calls to enhance HAB surveillance and monitoring. The study focuses on Cape Coral, FL, USA, located along the banks of the Caloosahatchee River and Estuary and the Gulf of Mexico. The wider study area experienced a prolonged cyanobacteria bloom in 2018. The present study examines the relationship between weekly water quality characteristics (temperature, dissolved oxygen, pH, microcystin-LR) and municipal requests for information or services (algal 311 calls). Each 1 μg/L increase in waterborne microcystin-LR concentrations corresponded with 9% more algal 311 calls (95% confidence interval: 1.03-1.15, p = 0.002). The results suggest water quality monitoring and the 311 dispatch systems may be further integrated to improve public health surveillance. HIGHLIGHTS Integrating the 311, environmental, and public health surveillance systems could provide callers with more information and target additional testing.; Cyanobacteria's waterborne microcystin-LR concentrations were associated with the timing and number of algal complaints from local residents.; People living in close proximity to prolonged and intense harmful algal blooms may experience respiratory health symptoms.;